Immune Signature-Based Risk Stratification and Prediction of Immunotherapy Efficacy for Bladder Urothelial Carcinoma - Liang, Fangfang; Xu, Yansong; Chen, Yi; Zhong, Huage; Wang, Zhen; Nong, Tianwen; Zhong, Jincai (Frontiers in Molecular Biosciences, 2021)
Immune-related genes (IRGs) are closely related to the progression of tumor and immune microenvironment. Few studies have investigated the effect of tumor immune microenvironment on the survival and response to immune checkpoint inhibitor (ICIs) of patients with bladder epithelial carcinoma (BLCA). We constructed two IRG-related prognostic signatures based on gene-immune interaction for predicting risk stratification and immunotherapeutic responses. We also verified their predictive ability on internal and overall data sets. Patients with BLCA were divided into high- and low-risk groups. The high-risk group had poor survival, enriched innate immune-related cell subtypes, low tumor mutation burden (TMB), and poor response to anti-PD-L1 therapy. Our prognostic signature can be used as a reliable prognostic biomarker and may be helpful to screen the people who will benefit from immunotherapy and guide the clinical decision-making of patients with BLCA.